Hubungan Daya Tahan Dan Kelincahan Dengan Kemampuan Bermain Bulu Tangkis Pada Siswa Ekstrakurikuler - Muhammad Reyfan Dzaki Rafif; Ahmad Rifai Panjaitan; Ahmad Avandi; Syahputra Manik (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to determine the relationship between endurance and agility with badminton playing ability among students. The research employed a quantitative approach with a correlational design. The sample consisted of 25 students selected through purposive sampling. The instruments used included the beep test to measure endurance, the shuttle run test to assess agility, and a skill test to evaluate badminton playing ability. Data were analyzed using descriptive and inferential statistics through correlation tests. The results showed that there is a significant relationship between endurance and badminton playing ability, as well as a stronger relationship between agility and playing ability. Simultaneously, endurance and agility contribute significantly to students' badminton playing ability. Therefore, physical condition, especially endurance and agility, is an important factor that needs to be developed to improve badminton playing skills.